Hubungan Perilaku dengan Kualitas Komponen Rumah Penderita Penyakit Infeksi Saluran Pernafasan Akut tahun 2017 (Studi Kasus di Desa Wage Kec. Taman Kab. Sidoarjo) - Dana Aprilia; Umi Rahayu; Khambali . (GEMA LINGKUNGAN KESEHATAN, 2018)
Bad behavior of maintaining the quality of house components can be a risk factor to environmentally based disease transmission. a.o, Acute Respiration Infection. The germs of Acute Respiration Infection can be transmitted through coughing or sneezing using air as transmission media. This research aimed to find out the relation between behavior and the quality of house component of people affected by acute respiration infection. This research was analytical with cross sectional approach. Data collection was through observation, interviews and measurements. Sample collected were 51 houses of people suffering from Acute Respiration Infection. Variables of this research were: awareness, behavior, action / proceeding, ventilation available, lighting, humidity, temperature, bedroom occupants density, and cleanliness of the house. Sampling technique used was random sampling. Data analyzes utilized was Chi Square test statistical analysis by means of SPSS 20 version. The result of the research showed that there was a relation between awareness (p=0,005), attitude (p=0,032), action/proceeding (p=0,002) behavior (p=0,002) with the quality of house components of people affected by Acute Respiration Infection. Based on this research, it could be concluded that there was a relation between awareness level, attitude, proceeding, and behavior with the quality of house component of people affected by Acute Respiration Infection. Prevention of transmission of Acute Respiration Infection could be done by upgrading the patient and house inmates behavior to create a healthy house condition.Keywords : Behavior, Quality of the House Components, Acute Respiration Infection